The Effect of Talking Stick Learning Model Assisted by Question Card Media on Junior High School Students' Mathematical Problem-Solving Ability - Indah Pertiwi; Shafa Nurul Izzah (Numerical: Jurnal Matematika dan Pendidikan Matematika, 2025)
This study investigated the effectiveness of the Talking Stick learning model assisted by Question Card media in enhancing junior high school students’ mathematical problem-solving abilities. A quantitative approach with a quasi-experimental design was employed, involving 63 students divided into an experimental and a control group. Data was collected through pretests and posttests, supported by interviews and documentation. The data were analyzed using an independent-samples t-test and a one sample t-test with SPSS. The results indicated a significant difference in mathematical problem-solving abilities between students taught using the Talking Stick Learning Model assisted by Question Cards and those taught using conventional methods. Furthermore, the mean posttest score of students in the experimental group (79.57) significantly exceeded the Minimum Completion Criteria (KKM) of 70. These findings suggest that the Talking Stick learning model assisted by Question Card media is effective in improving students’ mathematical problem-solving abilities.